2002
DOI: 10.1159/000068326
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Stress Increases Human T Cell Apoptosis in vitro

Abstract: Objectives: Recent studies have shown that apoptosis is involved in stress responses. The present study examined if stressors increase in vitro apoptosis of peripheral blood T lymphocytes in a dose-dependent manner. Methods: Daily subjective stress was quantitatively analyzed in 40 nonsmoking men with a daily hassles questionnaire. Apoptosis of T lymphocytes was measured by flowcytometry using Annexin V/PI double staining method after 0, 12, and 24 h of culture in the presence or absence of dexamethasone (DEX)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
3
4
0
1
Order By: Relevance
“…Similar to our findings, apoptosis has previously also been shown in a variety of immune cells under physiological or pathological conditions, such as activation-induced apoptosis in peripheral T cells, mediated through Fas-Fas ligand interaction, [13] or accelerated spontaneous apoptosis in CD4+ T cells in depressed patients [48] . Moreover, previous in vitro studies demonstrated that T cell depletion after psychological stress occurs by apoptosis in accordance with our findings [49] .…”
Section: Discussionsupporting
confidence: 93%
“…Similar to our findings, apoptosis has previously also been shown in a variety of immune cells under physiological or pathological conditions, such as activation-induced apoptosis in peripheral T cells, mediated through Fas-Fas ligand interaction, [13] or accelerated spontaneous apoptosis in CD4+ T cells in depressed patients [48] . Moreover, previous in vitro studies demonstrated that T cell depletion after psychological stress occurs by apoptosis in accordance with our findings [49] .…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the observed partial mediating effect of stress neuropeptides in the association between pain ratings and lymphocyte Fas expression is consistent with previous evidence implicating stress in the modulation of apoptosis and activation of the JNK pathway 35. Psychological stress36 and stress hormones37 have been reported to induce lymphocyte apoptosis in humans and in animal models 38. Based on the above, the role of stress peptides in the regulation of pain-related apoptosis merits to be investigated further.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, flow cytometric assessments have revealed that CD4+ T cells from depressed patients exhibit evidence of accelerated spontaneous apoptosis as well as increased expression of the receptor for Fas (CD95), which mediates apoptotic signaling by Fas-ligand (Eilat et al, 1999; Ivanova et al, 2007; Szuster-Ciesielska et al, 2008). Increased T cell apoptosis has also been observed as a function of chronic stress in both humans and laboratory animals (Sakami et al, 2002; Shi et al, 2003). One possibility that might explain increased T cell apoptosis in depression, especially in the context of increased immune activation, is tryptophan depletion.…”
Section: T Cells and Depressionmentioning
confidence: 99%